Identification of Customary International Law in the Works of the United Nations International Law Commission - Grabowska, Genowefa (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
The review of the ways in which customary norms were established and of the role that the custom played in the system of sources of the international law was undertaken by the International Law Committee in 2012, when the subject of "Formation and evidence of customary international law" was included in its agenda and started being discussed . The topic was approved, first by the Sixth Committee and then, by the whole General Assembly of the United Nations which opened the way to further codification . In 2013 the Commission appointed Sir Michael Wood as the Special Rapporteur. The Rapporteur then submitted his first report supplemented by the memorandum of the International Law Commission Secretariat and the title of the report was "Elements in the previous work of the International Law Commission that could be particularly relevant to the topic" . During further discussions the ILC changed the title of the codified issue, replacing the initial topic ("Formation and evidence of customary international law") with the following one, which better reflected the nature of the regulation: "Identification of customary international law". By doing so the Commission wanted to clarify doubts as to the meaning of the word "evidence", in particular when translated into official languages of the United Nations.
Keywords: identyfikacja zwyczajowego prawa międzynarodowego; Komisja Prawa Międzynarodowego Organizacji Narodów Zjednoczonych; dowód zwyczaju